2010
DOI: 10.1080/13549830903575562
|View full text |Cite
|
Sign up to set email alerts
|

Landlords, fear, and children's respiratory health: an untold story of environmental injustice in the central city

Abstract: Recent research has explored the role of environmental inequalities in explaining health disparities, especially in urban environments. This paper investigates the role of the landlord in shaping indoor environmental injustices. Specifically, we rely on interview data from low-income parents in South Phoenix, AZ, with elementary-aged children with asthma. We found families living in poor quality rental housing that impacted children's breathing. Landlords were directly involved in keeping the homes in poor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…40 Substandard housing in poor and minority neighborhoods has been considered an environmental injustice, as it can result from inequitable social processes, such as a landlord's disinvestment in a rental property or a low-income homeowner's having to make decisions between making home repairs and paying bills. 41 The 2007 study showed that 6% of Black-occupied housing, 5% of Hispanic-(of any race) occupied housing, and 3.5% of White-occupied housing reported moderate or severe physical housing problems such as missing roofing material, holes in the roof, boarded up windows, and broken windows. 42 Another potential reason for the inequitable distribution of ecosystem services from trees may be higher initial levels of pollution in minority neighborhoods.…”
Section: Environmental Justice Implications Of Tree Covermentioning
confidence: 99%
“…40 Substandard housing in poor and minority neighborhoods has been considered an environmental injustice, as it can result from inequitable social processes, such as a landlord's disinvestment in a rental property or a low-income homeowner's having to make decisions between making home repairs and paying bills. 41 The 2007 study showed that 6% of Black-occupied housing, 5% of Hispanic-(of any race) occupied housing, and 3.5% of White-occupied housing reported moderate or severe physical housing problems such as missing roofing material, holes in the roof, boarded up windows, and broken windows. 42 Another potential reason for the inequitable distribution of ecosystem services from trees may be higher initial levels of pollution in minority neighborhoods.…”
Section: Environmental Justice Implications Of Tree Covermentioning
confidence: 99%
“…There is remarkably little research on the role of the housing manager in the private rental sector, especially in terms of mediating and managing the relationship between landlords and tenants. It is particularly notable that most research on relationships in the private rental sector focuses directly on the landlord and tenant, or conflates landlords and property managers (see for example Lister 2004;Lister 2005;Bierre et al 2010;Grineski and Hernández 2010). Nonetheless, this work is relevant to understanding how tenants may experience housing managers and landlords.…”
Section: Managing and Influencing Tenants Landlords And Relationshipsmentioning
confidence: 99%
“…Lister's (2004; work examined the challenges faced by young people when first entering the rental sector, and their experiences of being 'monitored' by landlords as landlords seek to control both tenants and the property. Grineski and Hernández (2010) explored environmental injustices of the private rental sector in Arizona. They argued that the poor quality of housing stock, and the failure of landlords to improve it, contributed to the ongoing health problems of tenants; tenants were placed in an unequal relationship with their landlords and were ignored when they sought improvements to their dwellings.…”
Section: Managing and Influencing Tenants Landlords And Relationshipsmentioning
confidence: 99%
“…While the majority of EJ studies focus on outdoor environments (e.g., factory releases and criteria air pollution), indoor environmental exposures can also be considered environmental injustices (Grineski & Hernandez, 2010). Poor home environments have less often been considered in terms of environmental injustice in the past (see Kraft & Scheberle, 1995; Landrigan, Rauh, & Galvez, 2010 for exceptions), possibly because there is a tendency to assume that in-home conditions are products of independent household decisions, rather than power-laden products of social processes (Grineski & Hernandez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Poor home environments have less often been considered in terms of environmental injustice in the past (see Kraft & Scheberle, 1995; Landrigan, Rauh, & Galvez, 2010 for exceptions), possibly because there is a tendency to assume that in-home conditions are products of independent household decisions, rather than power-laden products of social processes (Grineski & Hernandez, 2010). Certainly, indoor environmental exposures (e.g., roaches, rodents, mold) are more prevalent in substandard housing inhabited by the poor (Matte & Jacobs, 2000) and have been linked to respiratory symptoms at the individual (Lanphear, Aligne, Auinger, Weitzman, & Byrd, 2001) and neighborhood levels (Grineski, 2007).…”
Section: Introductionmentioning
confidence: 99%